Strengthening micro-entrepreneurship for the disadvantaged youth in Middle East and North Africa - Pyrog, O. V.; Shevchenko, N. V. (Publishing House of Lviv Polytechnic National University, 2015)
The article presents the research of tools that stimulate micro-entrepreneurship for unemployed youth, facilitate self-employment, formalize entrepreneurship and lessen the gender gap in business. The proposals developed are aimed at creating new business opportunities for the unemployed young people. Centers of Professional Orientation and Integration (CPOI) create and utilize online database, combining business and education resources. This database is the key element of the system as it accumulates information about labor market for CPOI, creates business education environment for disadvantaged youth and provides non-financial support for entrepreneurs. We address the problem of unemployment by implementing an innovative database system realized using cloud technology with real-time data about participants and business partners. Cloud technology will provide CPOIs with efficient communications, which allows easy monitoring of CPOIs activities across the country. The database will aggregate real-time data and segment it according to economic, social, professional and regional characteristics in order to create appropriate CPOI strategy.
Keywords: entrepreneurship; microentrepreneurship; business; Centers of Professional Orientation and Integration (CPOI); youth; employment; unemployment; self-employment; Middle East and North Africa (MENA); Morocco